Optimization of the Web based Learning Management System (LMS) Application for PJOK Learning at SMA/SMK Equivalent Level in North Sumatra - Rini Andriani; Bayu Hardiyono; Amir Supriadi; Afri Tantri; Abdul hakim Siregar (UNIB Press, 2023)
This study aims to develop a website-based E-learning management system (LMS) application product that can become a PJOK learning medium byLearning Management System (LMS) in which all learning is focused on one medium, as well as an information medium for available Physical Education, Sports and Health (PJOK) class packages so that they can be read in detail and completely. This study involved 62 physical education sports and health teacher subjects (PJOK) and 50 student subjects. The research was conducted in two stages. The first stage of the small-scale trial consisted of 5 students from SMK Negeri 10 Medan. The second stage of the large-scale trial consisted of 3 state schools namely SMA Negeri 1 Binjai, SMK Negeri 2 Medan and SMK Negeri 10 Medan where each school consisted of 1 student as a representative. This type of research uses the type of development research (research and development) by involving media/IT experts. Material experts, expert practitioners of learning, namely practitioners who use teachers and students. Based on the results of the trial by media/IT experts, the application rating was obtained with a score of 4.54 in the Very Good category and declared